2010
DOI: 10.1002/syn.20770
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic regulation of dopamine D3 and D3nf receptor mRNA expression

Abstract: Dopamine D3 receptors have the highest dopamine affinity of all dopamine receptors, and may thereby regulate dopamine signaling mediated by volume transmission. Changes in D3 receptor isoform expression may alter D3 receptor function, however little is known regarding coordination of D3 isoform expression in response to perturbations in dopaminergic stimulation. In order to determine the effects of dopamine receptor stimulation and blockade on D3 receptor alternative splicing, we determined D3 and D3nf isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Changes in the expression of D 3 nf could be associated with the reduced activation of D 3 R after DA depletion, as has been suggested for D 2 R activity, which regulates the expression of its splicing isoforms D 2L R and D 2S R (Sasabe et al 2011). In support of this hypothesis, it was recently reported that D 3 nf levels in the brain are influenced by DA signals: D 3 R mRNA expression was not modified after its blockade, although D 3 nf mRNA was reduced (Richtand et al 2010), leading to an increase in the D 3 R-to-D 3 nf mRNA ratio during the "hypodopaminergic state" (Richtand et al 2010). This result closely matches our biochemical and pharmacological findings.…”
Section: Discussionmentioning
confidence: 54%
“…Changes in the expression of D 3 nf could be associated with the reduced activation of D 3 R after DA depletion, as has been suggested for D 2 R activity, which regulates the expression of its splicing isoforms D 2L R and D 2S R (Sasabe et al 2011). In support of this hypothesis, it was recently reported that D 3 nf levels in the brain are influenced by DA signals: D 3 R mRNA expression was not modified after its blockade, although D 3 nf mRNA was reduced (Richtand et al 2010), leading to an increase in the D 3 R-to-D 3 nf mRNA ratio during the "hypodopaminergic state" (Richtand et al 2010). This result closely matches our biochemical and pharmacological findings.…”
Section: Discussionmentioning
confidence: 54%
“…Our data suggest that changes in the expression of D 3 nf isoform are most likely responsible. According to the model proposed by Richtand et al (2010) and Karpa et al (2000), dimerization of D 3 nf isoform with D 3 R, sequester the latter into the cytoplasm preventing its location on membrane and signaling. On the contrary, according to Elmhurst et al (2000), the interaction can occur at the cytoplasmic membrane and also prevents D 3 R signaling.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it has been proposed that surface expression (Karpa, Lin, Kabbani, & Levenson, 2000) and function (Elmhurst, Xie, O'Dowd, & George, 2000) of D 3 R depends on the expression of its truncated splice variant named D 3 nf (Liu, Bergson, Levenson, & Schmauss, 1994), a protein with similar levels as canonical one (Liu et al, 1994) and that does not bind dopamine (Richtand, 2006). D 3 nf dimerizes with the canonical D 3 R sequestering them in the cytoplasm (Richtand et al, 2010) or interacting with these in the membrane (Elmhurst et al, 2000), preventing their signaling and regulating their interaction with other receptors, such as D 1 R (Richtand et al, 2010). Moreover, expression of D 3 nf protein decreases in experimental Parkinson (Prieto et al, 2011), which increases D2‐like inhibitory responses on Ca 2+ currents of striatopallidal neurons (Prieto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the second stage, the modifications established at the first stage are consolidated through the modification of expression of the respective genes. The ability of DA receptors to undergo automodifications has been demonstrated both at the level of radioligand binding and at the level of gene expression in various brain structures and various experimental procedures [319, 442447]. …”
Section: Dopaminergic System Of the Brainmentioning
confidence: 99%